Diagnostico de la gestión productiva agrícola del sector minorista en el cantón bolívar período 2017 - Alcívar Cedeño, Kassandra K. (2017)
The present investigation aimed at the diagnosis of agricultural production management of the retail sector in the canton of Bolivar, its compliance is based on three methodological stages, whereas the first point the characterization of the agricultural producers of the canton was carried out. The application of surveys in order to know the degree of compliance of the farmer in terms of agricultural practices and shortcomings. In the second instance, it is possible to identify the critical success factors, for which a list of characteristics related to BPA (Good Agricultural Practices) was made for farmers through an interview. Such information was fundamental for the identification of weaknesses, strengths, opportunities and threats presented in the field of agroproduction. For the conclusion of this research, an improvement plan was proposed that would contribute to boost the performance in the agricultural area of the Bolivar canton by establishing measures to solve the problems produced. This was a support for the criteria which had been classified as a problem.